Pengaruh Aromaterapi Lemon terhadap Penurunan Skala Nyeri Pasien Post Operasi Laparatomi - El Rahmayati; Raihan Hardiansyah; Nurhayati Nurhayati (Politeknik Kesehatan Tanjung Karang, 2018)
The operation 2012 in Indonesia reached 1.2 million (WHO in Sartika, 2013). Based on the National Health Data Tabulation of the Republic of Indonesia in 2009, surgical procedures occupy the 11th outline of the first 50 treatment of disease patterns in hospitals in Indonesia, which is estimated to be 32% of which are laparotomy (RI Ministry of Health, 2009). Previous data obtained from the MOH report (2007) states that cases of laparotomy operations continued to increase, from 162 in 2005 to 983 cases in 2006 and 1,281 cases in 2007. Complications in post-laparotomy patients were severe pain, bleeding, even death. Pain management is done by pharmacological and non-pharmacological techniques. In patients who experience mild pain up to the treatment can be done with non-pharmacological techniques. Non-pharmacological actions include aromatherapy using lemon oil essence. Based on the description above, researchers are interested in conducting research. This study aims to determine. This type of quantitative method research uses a quasi-experimental design with a one group pre-test post-test design approach. Sampling techniques using accidental sampling techniques were 32 respondents. Data collection uses measurements of the Numeric Rating Scale (NRS). Statistical test using Wilcoxon signed ranked test. The results of this study concluded that there were differences in pain intensity in patients post laparotomy surgery before and after lemon aromatherapy was given with p-value 0.000. Based on the conclusions of the results of the study, the authors suggest that hospitals can consider the use of lemon aromatherapy to treat pain in post-laparotomy patients using existing standard operating procedures.